Tracking rendition aircraft as a way to understand CIA secret detention and torture in Europe. Issue 1 (2nd January 2016) - Raphael, Sam; Black, Crofton; Blakeley, Ruth; Kostas, Steve
Abstract : We examine how the tracking of rendition aircraft has provided a much fuller understanding of the CIA's rendition, detention and interrogation programme. In particular, we show how this illuminated the role played by European states. Through various investigative methods, new rendition aircraft were identified, significant amounts of flight data were gathered, and data on all known and suspected rendition flights were collated into one public, searchable database. We show that examining logistical elements of covert programmes can prove fruitful for security and human rights research. Furthermore, we demonstrate the benefits of close academic–practitioner collaboration in the field of human rights.